In‐vitro effect of pembrolizumab on different T regulatory cell subsets. (3rd November 2017) - Toor, S. M.; Syed Khaja, A. S.; Alkurd, I.; Elkord, E.
Summary: Programmed death‐1 (PD‐1) and interactions with PD‐ligand 1 (PD‐L1) play critical roles in the tumour evasion of immune responses through different mechanisms, including inhibition of effector T cell proliferation, reducing cytotoxic activity, induction of apoptosis in tumour‐infiltrating T cells and regulatory T cell (Treg ) expansion. Effective blockade of immune checkpoints can therefore potentially eliminate these detrimental effects. The aim of this study was to investigate the effect of anti‐PD‐1 antibody, pembrolizumab, on various Treg subpopulations. Peripheral blood mononuclear cells (PBMC) from healthy donors (HD) and primary breast cancer patients (PBC) were treated in vitro with pembrolizumab, which effectively reduced PD‐1 expression in both cohorts. We found that PD‐1 was expressed mainly on CD4 + CD25 + T cells and pembrolizumab had a greater effect on PD‐1 expression in CD4 + CD25 − T cells, compared to CD4 + CD25 + cells. In addition, pembrolizumab did not affect the expression levels of Treg ‐related markers, including cytotoxic T lymphocyte antigen‐4 (CTLA‐4), CD15s, latency‐associated peptide (LAP) and Ki‐67. Moreover, we report that CD15s is expressed mainly on forkhead box P3 (FoxP3) − Helios + Treg in HD, but it is expressed on FoxP3 + Helios − Treg subset in addition to FoxP3 − Helios + Treg in PBC. Pembrolizumab did not affect the levels of FoxP3 +/− Helios +/− Treg subsets in both cohorts. Taken together, our study suggests that pembrolizumab does not affect Treg or change their phenotype or function but rather blocks signalling via the PD‐1/PD‐L1 axis in activated T cells. Abstract : The aim of this study was to investigate the effect of anti‐PD‐1 antibody, pembrolizumab, on various Treg subpopulations. Pembrolizumab effectively reduced PD‐1 expression in cells isolated from healthy donors and breast cancer patients, however it did not affect expressions of CTLA‐4, CD15s, LAP and Ki‐67. This study suggests that pembrolizumab does not affect Treg or change their phenotype or function but rather blocks signaling via PD‐1/PD‐L1 axis in activated T cells.